PENGARUH PROFITABILITAS DAN VALUASI HARGA SAHAM TERHADAP RETURN SAHAM (Studi Kasus pada Perusahaan Konsumer Non-siklikal PT. Indofood CBP Sukses Makmur, Tbk Q1 2011 – Q4 2021) - Perwira, Deghar Rajendra; Devia , Vietha (Contemporary Studies in Economic, Finance and Banking, 2022)
The existence of the stock exchange is widely known by the public, as reflected in the SID which shows a significant increase from 2017 to 2021. One popular stock exchange investment instrument is stocks, with the highest probability of return but accompanied by great risk. Specifically, non-cyclical consumer companies can provide investment security because of stable profit growth in the long term, making it attractive for investors with long investment timeframes. However, efforts to achieve optimal returns require an analytical process, involving financial statements as a fundamental aspect. There are important ratios, one of which is profitability shown through Net Profit Margin and Return On Equity. In addition, the rational analysis process can be strengthened by evaluating stock prices. This research aims to determine the impact of profitability and stock price valuation on stock returns of PT. Indofood CBP Sukses Makmur, Tbk (ICBP). One of the reasons why ICBP was chosen as the object of research is because as a leading company in the non-cyclical consumer sector with good profitability, however, ICBP's stock price tends to decline at this time. This research uses a quantitative method with multiple linear regression through Eviews 12. The results of the research prove that there is a significant and positive impact of Return On Equity and stock price valuation on stock returns. Meanwhile, Net Profit Margin does not have a significant impact on stock returns.